Spatial distributions of the fields in guided normal modes of two coupled parallel optical nanofibers. (2nd April 2021) - Kien, Fam Le; Ruks, Lewis; Chormaic, Síle Nic; Busch, Thomas
Abstract: We study the cross-sectional profiles and spatial distributions of the fields in guided normal modes of two coupled parallel optical nanofibers. We show that the distributions of the components of the field in a guided normal mode of two identical nanofibers are either symmetric or antisymmetric with respect to the radial principal axis and the tangential principal axis in the cross-sectional plane of the fibers. The symmetry of the magnetic field components with respect to the principal axes is opposite to that of the electric field components. We show that, in the case of even E z -cosine modes, the electric intensity distribution is dominant in the area between the fibers, with a saddle point at the two-fiber center. Meanwhile, in the case of odd E z -sine modes, the electric intensity distribution at the two-fiber center attains a local minimum of exactly zero. We find that the differences between the results of the coupled mode theory and the exact mode theory are large when the separation distance between the fibers is small and either the fiber radius is small or the wavelength of light is large. We show that a slight difference between the radii of the nanofibers leads to strong asymmetry of the intensity distributions of the guided normal modes.